2009
DOI: 10.1007/s10800-009-9871-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic recovery of light carboxylic acids from industrial aqueous wastes

Abstract: A study has been carried out on the possibility of recovery light carboxylic acids (C1-C6) from an acidic waste stream by means of electrodialysis (ED) technique. The starting solution has very low concentration in organic acids and low specific conductivity. The main object of the study is the identification of the critical aspects for a complete electrodeionization of the water in a scheme of water reuse as process water or boiler feed-water. Concentration and recovery of carboxylic acids from wastewater str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Especially, ED in combination with high pH offers an interesting potential. VFA that are generated under an alkaline pH are in the anionic form and can be directly extracted from the fermentation broth using ED (Huang et al, 2007;Vertova et al, 2009). Meanwhile, it should also be noted that alkaline pH may affect the VFA composition of the end product and may cause toxicity to the fermenting microorganisms by free ammonia.…”
Section: Overall Cod N and P Mass Balancesmentioning
confidence: 99%
“…Especially, ED in combination with high pH offers an interesting potential. VFA that are generated under an alkaline pH are in the anionic form and can be directly extracted from the fermentation broth using ED (Huang et al, 2007;Vertova et al, 2009). Meanwhile, it should also be noted that alkaline pH may affect the VFA composition of the end product and may cause toxicity to the fermenting microorganisms by free ammonia.…”
Section: Overall Cod N and P Mass Balancesmentioning
confidence: 99%
“…Vertova et al found elctrodialysis for treating light carboxylic acids from an acidic waste stream. In addition, the authors determine that the use of electrodialysis is a sustainable alternative to biological degradation [106].…”
Section: Reusementioning
confidence: 99%
“…The components considered using UV light source, UV irridation, hydrogen peroxide and ultrasound constituent. Vertova et al (2009) found elctrodialysis for treating light carboxylic acids from an acidic waste stream.…”
Section: Micheletti Et Al (2009) Chose Surfactants Inmentioning
confidence: 99%